2017
DOI: 10.1590/s0102-053620170111
|View full text |Cite
|
Sign up to set email alerts
|

Adaptabilidade e estabilidade de populações de cenoura pelo método REML/BLUP

Abstract: RESUMO O objetivo foi avaliar a adaptabilidade e estabilidade de genótipos de cenoura pelo método REML/BLUP. Os experimentos foram conduzidos em 20 ambientes nos anos de 2010, 2011, 2012 e 2014 em diferentes regiões produtoras de cenoura do Brasil. O delineamento experimental utilizado foi de blocos ao acaso com três repetições e parcelas de 1 m2. Foram avaliadas quatro populações de cenoura em fase de melhoramento: CNPH-14, CNPH-15, CNPH-16 e CNPH-17, as cultivares de polinização aberta BRS Planalto e Brasíli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…Regarding the two open pollination cultivars, Carvalho et al (2015), measuring MRM at 100 DAS, found superior yield of commercial roots from BRS Planalto over Brasília, with values of 25.81 and 16.06 t ha -1 , respectively. Likewise, Carvalho et al (2017), in the evaluation in 20 environments, found an average MRM value of 34.54 t ha -1 for 'Brasília' and 35.95 t ha -1 for BRS Planalto. Pereira et al (2015) evaluated the cultivar BRS Planalto in summer conditions in Brasília-DF, and found a high MRM (58.07 t ha -1 ), roots with an average mass of 109.73 g, with an average length of 17.43 cm and diameter of three cm.…”
Section: Resultsmentioning
confidence: 85%
“…Regarding the two open pollination cultivars, Carvalho et al (2015), measuring MRM at 100 DAS, found superior yield of commercial roots from BRS Planalto over Brasília, with values of 25.81 and 16.06 t ha -1 , respectively. Likewise, Carvalho et al (2017), in the evaluation in 20 environments, found an average MRM value of 34.54 t ha -1 for 'Brasília' and 35.95 t ha -1 for BRS Planalto. Pereira et al (2015) evaluated the cultivar BRS Planalto in summer conditions in Brasília-DF, and found a high MRM (58.07 t ha -1 ), roots with an average mass of 109.73 g, with an average length of 17.43 cm and diameter of three cm.…”
Section: Resultsmentioning
confidence: 85%
“…In the organic production system, in which the use of chemicals for disease control is prohibited, the genetic resistance factor becomes highly desirable. In this context, Embrapa's carrot breeders have been working on developing cultivars more adapted to this cropping system, with good yield and root quality, but mainly higher levels of resistance or tolerance to this disease complex (Carvalho et al, 2013(Carvalho et al, , 2017. As a result of the efforts in the last decade, the cultivar BRS Paranoá was released in 2020.…”
Section: Resumo Brs Paranoá: Cenoura Para Sistemas Orgânicos De Produçãomentioning
confidence: 99%
“…A cenoura (Daucus carota L.) é a principal hortaliça do grupo das raízes tuberosas com área média de 22 mil ha plantados (RESENDE et al, 2016) e consumo per capita de 1,75 kg/hab/ano (IBGE, 2010). Possui alto valor econômico e é consumida de forma in natura ou processadas, onde a raiz, parte comestível é considerada importante fonte de vitamina A e potássio na dieta humana (FILGUEIRA, 2013), cultivada em larga escala nas regiões Centro-Oeste, Sudeste, Nordeste e Sul do Brasil (CARVALHO et al, 2017).…”
Section: Introductionunclassified